New insights of microRNAs and metabolic pathways in tomato species and Schistosoma haematobium - Cardoso, Thaís Cunha de Sousa (2021)
The Solanaceae family is one of the largest families in the plant kingdom, including several plants of agronomic and medical importance, especially tomatoes, due to their high consumption worldwide. In addition to its importance as a food, tomatoes have interesting agronomic characteristics, namely, fleshy fruit and compound leaves, which model plants do not have, eg. Arabidopsis thaliana. In this sense, the common tomato (Solanum lycopersicum) has been used as a model for species that also have such characteristics. Due to their specific characteristics and growing conditions, tomato varieties are constantly being improved. However, this crop is susceptible to several pests and pathogens. To help control these diseases, most producers choose to use chemical agents, which are often expensive, sometimes ineffective and have harmful effects on the environment. An alternative to these problems is to cross the cultivated tomato with wild species. There are several known species of wild tomatoes, constituted by little explored genetic resources and of great importance for the improvement, research and development of the culture, such as Solanum pennellii, Solanum galapagense, Solanum chilense, Solanum peruvianum and Solanum pimpinellifolium. Some species of wild tomatoes have been widely used for the construction and mapping of populations due to their tolerance to environmental stress. In this sense, a better understanding of the molecular basis of tomatoes is necessary to achieve efficiency and success in the selection of markers associated with the characteristics of interest, such as biotic and abiotic tolerance. In the same way that it is important to obtain a greater knowledge about the molecular bases of many species of plants, some animals, parasites, bacteria and viruses also need molecular studies to assist in the control of diseases that affect humans. In this sense, human schistosomiasis is a parasitic disease caused by helminths of the genus Schistosoma that affects millions of people worldwide. Five species of Schistosoma are responsible for the majority of human infections: Schistosoma mansoni, Schistosoma japonicum, Schistosoma haematobium, Schistosoma mekongi and Schistosoma intercalatum. S. haematobium affects the reproductive and urinary systems and has been considered a major public health problem in Africa. The spread of the disease is dependent on the interaction between the parasite and the intermediate host. This interaction is complex and determined by some genes involved in the parasite's infectivity and host susceptibility. Therefore, understanding the mechanisms of gene regulation is extremely important to understand the parasite-host interactions and which genes can contribute to the infection. Current progress in sequencing the genome of plants and animals has generated useful information to assist in the study of the genetic diversity of many species. In the 2000s, the genomes of S. galapagense, S. peruvianum, S. haematobium, S. lycopersicum, S. pennellii, S. pimpinellifolium and S. chilense were sequenced. The interpretation of schistosome genomes has improved our understanding of the molecular biology of these parasites, allowing the identification and characterization of genes not yet discovered. The availability of a tomato reference genome provided a framework for the genomic analysis of the Solanaceae family, generating a source of important information for its molecular improvement. In addition, the sequencing of genomes of wild tomato species has provided a valuable resource for understanding several prominent characteristics, such as changes in response to water deficit, biotic and abiotic resistance and metabolism. However, several parts of these genomes need to be thoroughly studied and annotated, since sequencing the genome and depositing the sequences in public databases are only the initial steps of the study. Recent studies have shown the importance of gene regulation involving several classes of small RNAs, their processing system and cell performance in different organisms. The main representatives of this class of small RNAs are microRNAs (miRNAs), whose forms of regulation may involve inhibiting the translation process, mRNA degradation or gene silencing, either by target complementarity or by signaling changes in DNA in regions specific to the genome. Different proteins act to generate mature miRNAs specific for post-transcriptional regulation. In plants and animals, these miRNA synthesis pathways have some differences. Computational strategies have been used to identify miRNAs and proteins involved in their pathways in various organisms. Computational methods are widely used to identify genes, since some transcripts are expressed only under certain conditions or in specific cells. Thus, computational techniques assist in the process of discovering new miRNAs, using all the information contained in the genome and / or the transcriptome regardless of the sample. In addition, such methods are useful for predicting miRNA precursors and their targets. Given the importance of such non-coding RNAs in the regulation of gene expression, it is important to study mature miRNAs and precursors, as well as the genes involved in the miRNA pathway in these species of cultivated and wild tomatoes to assist in the elucidation of biological processes, as well as their performances at the cellular level. Also in S. haematobium, the knowledge of these small molecules and their processing pathway can help to understand the life cycle of this parasite, its mechanism of infectivity and in the search for new methods to control schistosomiasis. In addition to the miRNA production pathway, other defense pathways are important in some plants. Different allelochemicals present in Solanum species have been associated with resistance to pests, such as methyl ketones, sesquiterpenes and acyl sugars. The selection for high levels of these allelochemicals could, in this way, constitute an efficient technique of indirect selection for resistance to pests. These purified phytochemicals can act against pests by reducing larval development, impairing the nutrition and oviposition of many tomato pests. In view of the great importance of tomatoes and the high rate of application of pesticides in the crop, greater knowledge about the molecular basis of tomatoes is necessary in the selection of markers associated with important characteristics in response to biotic and abiotic stress. Therefore, understanding the miRNAs, their processing pathway and the genes related to the production of metabolites may help to understand their involvement in resistance to arthropods, mainly due to the production of acyl sugar and post-transcriptional regulation mediated by miRNAs. In view of these issues, Chapter I will present the theoretical background on miRNAs, acylacars and their pathways, in addition to the importance of studying these molecules in S. lycopersicum, S. pennellii, S. galapagense, S. chilense, S. peruvianum, S. pimpinellifolium and S. haematobium. In Chapter II, articles published and submitted regarding research carried out during the doctorate will be exposed. Cultivated tomato, Solanum lycopersicum, is one of the most common fruits in the global food industry and together with the wild tomato Solanum pennellii, are both species widely used in developing better cultivars. microRNAs act on mRNA regulation, inhibiting their translation and/or promoting its degradation. Important proteins involved in these processes are ARGONAUTA and DICER. This study aimed to identify and characterize genes involved in miRNA processing pathways, miRNAs molecules and target-genes in the genome of both species using in silico analysis. We also validated the genes and miRNAs expression in different NGS libraries, in addition to validating some miRNAs using quantitative RT-PCR. We identified 70 putative proteins in S. lycopersicum and 108 in S. pennellii involved in small RNAs processing. Of these, 28 and 32 participate in miRNA processing pathways, respectively. We identified 343 mature miRNAs, 226 pre-miRNAs in 87 families, including 192 miRNAs not previously identified, belonging to 38 new families in S. lycopersicum. In S. pennellii, we found 388 mature miRNAs, 234 pre-miRNAs contained in 85 families. All miRNAs found in S. pennellii were unpublished, being first identified in our study. Furthermore, we identified 2471 and 3462 miRNA different target in S. lycopersicum and S. pennellii, respectively. Key genes control the infectivity of the Schistosoma haematobium causing schistosomiasis. A method for understanding the regulation of these genes might help in developing new strategies to control schistosomiasis, such as the silencing mediated by microRNAs (miRNAs). The miRNAs have been studied in schistosome species and they play important roles in the post-transcriptional regulation of genes, and in parasite-host interactions. However, genome-wide identification and characterization of novel miRNAs and their pathway genes and their gene expression have not been explored deeply in the genome and transcriptome of S. haematobium. Identify and characterize mature and precursor miRNAs and their pathway genes in the S. haematobium genome. Computational prediction and characterization of miRNAs and genes involved in miRNA pathway from S. haematobium genome on SchistoDB. Conserved domain analysis was performed using PFAM and CDD databases. A robust algorithm was applied to identify mature miRNAs and their precursors. The characterization of the precursor miRNAs was performed using RNAfold, RNAalifold and Perl scripts. We identified and characterized 14 putative proteins involved in miRNA pathway including ARGONAUTE and DICER in S. haematobium. Besides that, 149 mature miRNAs and 131 precursor miRNAs were identified in the genome including novel miRNAs. miRNA pathway occurs in the S. haematobium, including endogenous miRNAs and miRNA pathway components, suggesting a role of this type of non-coding RNAs in gene regulation in the parasite. The results found in this work will open up a new avenue for studying miRNAs in the S. haematobium biology in helping to understand the mechanism of gene silencing in the human parasite Schistosome. Acylsugars are allelochemicals secreted by type IV trichomes in leaves and have been associated with resistance to arthropod pests in Solanaceae species. In this study, the putative genes involved in the acylsugar metabolism were identified, characterized, and validated in cultivated tomato, Solanum lycopersicum, and wild tomato, Solanum pennellii. Eighty-seven putative genes were identified in S. lycopersicum and 77 in S. pennellii involved in the acylsugar pathway, including the key proteins branched-chain keto acid dehydrogenase E2 (BCKD E2), 2-isopropylmalate synthase A (IPMSA), and threonine deaminase/dehydratase (TD). The putative tomato proteins displayed conservation using conserved domain distribution and active site comparing to ortholog proteins from the acylsugar pathway. Phylogenetic analysis of the putative proteins BCKD E2, IPMSA, and TD showed that all putative tomato proteins grouped with their orthologs from the Solanaceae species, corroborating with the distribution of the tree of life. The BCKD E2 and the IPMSA transcripts from S. pennellii showed higher gene expression compared to S. lycopersicum transcripts, suggesting that the acylsugar pathway is more active in wild than in cultivated tomato, corroborating with the literature. Given the important role of the allelochemicals produced in Solanaceae, the results contribute to a better understanding of acylsugars and their processing pathways and open up opportunities to study their relationship with biotic resistance in these important species and other Solanaceae species.